PENERAPAN MODEL PEMBELAJARAN GENERATIF DALAM MENINGKATKAN KEMAMPUAN KONEKSI MATEMATIS DITINJAU DARI GAYA KOGNITIF - Sutihat Sutihat; Hepsi Nindiasari; Syamsuri Syamsuri (Mathematics Education Study Program, FKIP, Universitas Pasundan, 2019)
Mathematical connection ability is the ability of students to associate concepts in mathematics, mathematics with other disciplines and mathematics with everyday life. Based on several studies conducted by researchers it is known that students' mathematical connection ability is still low. In addition, teachers rarely pay attention to students' cognitive styles even though cognitive styles can affect students' mathematical connection abilities. Therefore, the purpose of this study is to find out the improvement of students' mathematical connection abilities by applying generative learning models in terms of cognitive style.This research was a quasi-experimental research with nonequivalent control group. The population in this study were all students of the second semester on XI MIPA class of MAN 4 Tangerang in the 2018/2019 academic year spread into 5 classes. The sampling technique in this study was taken by cluster random sampling technique, such as by taking two classes from the population randomly (drawn) that the population must be normal and homogeneous. The class used as the sample in this study were class XI MIPA 2 as an experimental class and class XI MIPA 5 as a control class where each class consists of 26 students. Based on the results of the research that has been done, it can be concluded that, (1) increasing mathematical connection ability of students with independent field cognitive styles who obtained generative learning higher than the increase in students' mathematical connection abilities in cognitive field independent style who obtain scientific learning, (2) an increase in students' mathematical connection abilities with field dependent cognitive styles who obtain generative learning is higher than the increase in students' mathematical connection abilities with field dependent cognitive styles who obtain scientific learning.